Identifikasi Nematoda Sista Kuning (Globodera Rostochiensis) Pada Kentang Di Batu, Jawa Timur : Identification Of Golden Potato Cyst Nematode (Globodera Rostochiensis) In Batu, East Java - Perpustakaan UGM, i-lib ([Yogyakarta] : Master of Management Program UGM, 2003)
Abstract: Identification of Globodera rostochiensis was done based on the information given by the Direktorat Perlindungan Hortikultura, that the potato plants in the sub district of Bumiaji, Batu, East Java, were attacked by potato cyst nematode (Globodera). Plants and soil samples were taken from the potato's areas in the sub-district of Bumiaji, especially in the villages of Brakseng (1 1,700 - 1,800m a.s.l), Tunggangan (Â± 1,600 1,700 m a.s.1), Kembangan (1 1,600 - 1,700 m a.s.l), and Junggo (Â± 1,200 m a.s.l). Based on morphological observations on eggs, larvae, females, and cysts, the nematode was identified as Globodera rostochiensis with special morphological characters: 1) second stage larvae vermiform with total body length 531 - 563p (x 548,4 p), body width 22 - 26 p (x 23,6 ,u), stylet well developed with styles knobs rounded, and part of the posterior portion hyaline in appearance